ESTIMATING VARIABILITY, HERITABILITY, AND GENETIC ADVANCE OF RICE GENOTYPES IN MID-HILLS OF NEPAL - Sashi Lamichhane; Nav Raj Adhikari; Bishwas K.C.; Sapana Thapa (Indonesian Journal of Agricultural Science, 2021)
Rice is an essential staple food in Nepal but researches and varietal improvement programs are rarely carried out due to inadequate variability study. The field study was carried to diagnose the influence of genetic and environmental factors on yield traits to aid future rice breeding programs. Twelve genotypes were arranged in randomized complete block design with three replications from July to November 2019 at the research field of the Institute of Agriculture and Animal Science, Tribhuvan University, in the hilly area of Nepal. Analysis of variance showed significant difference for days to 50% booting, days to 50% flowering, plant height, panicle length, flag leaf area, filled grains per panicle, unfilled grains per panicle, fertility percentage, effective tillers m-2, straw yield, grain yield, 1000-grain weight, and harvesting index indicating the presence of variation in genotypes. LPN BR-1615 was the most promising genotype in grain yield. The values of Phenotypic Coefficient of Variation (PCV) were higher than Genotypic Coefficient of Variation (GCV) for each trait and low difference between them was found for days to 50% booting, days to 50% flowering, plant height, panicle length, grain yield, thousand-grain weight, fertility percentage, and harvesting index. Plant height, effective tillers m-2, and grain yield showed high heritability (i.e. 93.2%, 60.5% and 92.6%, respectively) and higher genetic advance as percentage of mean (i.e. 46.5, 34.6 and 50.1, respectively) . Thus, the experiment revealed that selections favoring plant height, effective tillers m-2, and grain yield would help in effective breeding programs of rice in future.